Engineering design methods : strategies for product design - Cross, Nigel , 1942- (John Wiley & Sons, 2021)
"Design is all around us, and the wish to design things is inherent in human beings. One of the most basic characteristics of human beings is that they make a wide range of tools and other artefacts to suit their own purposes. As those purposes change, and as people reflect on the currently-available artefacts, some refinements are made to the artifacts, and sometimes completely new kinds of artifacts are conceived and made. The world is therefore full of tools, utensils, machines, buildings, furniture, clothes, and many other things that human beings apparently need or want in order to make their lives better. Everything that isn't a simple, untouched piece of nature has been designed by someone"-- Provided by publisher